The Role of Parents in Internalizing Islamic Character based on Muhammadiyah Values of Ilmu Amaliah and Amal Ilmiah - Alim, Siti Fatika; Haryanto, Sigit (Universitas Muhammadiyah Surakarta, 2025)
The Character education is a foundational element in shaping children's personality, particularly in the context of globalization where negative influences are prevalent. In Indonesia, Islamic character education rooted in religious values plays a crucial role in early childhood development. This study focuses on exploring the role of parents in the internalization of Islamic character values based on Muhammadiyah principles, especially Ilmu Amaliah (Practical Knowledge) and Amal Ilmiah (Scientific Practice), as implemented at Aisyiyah Unggulan Gemolong Elementary School. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews with parents and teachers, participatory observation in school activities, and analysis of school documents. The data were then analyzed thematically to identify patterns of parental involvement and the integration of Muhammadiyah values in character education. The findings reveal that parental involvement takes multiple forms, including participation in parenting seminars, school committee meetings, use of communication books, and supervision of daily Islamic routines at home. The school supports this process through structured programs such as daily charity, social service activities, public speaking (khitobah), adhan training, and life skills development. A key component identified is the home visit program, which allows teachers to better understand students' home environments and foster deeper collaboration with families. The synergy between school and parents effectively promotes the internalization of Ilmu Amaliah (knowledge implemented in daily life) and Amal Ilmiah (action informed by reflective and scientific thinking). Through shared values and joint initiatives, students experience Islamic teachings not only cognitively but also through daily habits and social practices. The research underscores the importance of school-family collaboration in fostering Islamic character aligned with Muhammadiyah's progressive Islamic vision.